Axions : theory, cosmology, and experimental searches - Kuster, M. (Springer, 2017)
Axions are peculiar hypothetical particles that could both solve the CP problem of quantum chromodynamics and at the same time account for the dark matter of the universe. Based on a series of lectures by world experts in this field held at CERN (Geneva), this volume provides a pedagogical introduction to the theory, cosmology and astrophysics of these fascinating particles and gives an up-to-date account of the status and prospect of ongoing and planned experimental searches. Learners and practitioners of astroparticle physics will find in this book both a concise introduction and a current reference work to a showcase topic that connects the "e;inner space"e; of the elementary particle world with the "e;outer space"e; of the universe at large.